Style between the rhetoric and the receipt Book of Al-Baianoaltabiin as sample - Younes, Wadha Ahmad; Alhosen, Abdulwahed Daham (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aims through dealing with Al- Jahez's rhetorical style, to assure the originality of many principals of the style science in our rhetorical and critical heritage, so this research starts the study from a hypothesis that is the style is considered equal and not a substitute or an inheritor of the ancient Arab rhetorical. It was necessary for the sake of the research to divide the study into two sections: the first one discuss the bases which must be offered in the literary styles to reach the rhetoric feature, and these bases are: The rightness grammatical, the commitment of the aesthetic criterions which are customary for the Arabs. the second section is represented by studying the ways which through them there is a presentation of the meanings in a rhetorical styles. The research ends to that the artistic picture with all its different arts is considered the best way to present the literary styles, because it marks the text by the artistic beauty which affects the audience sense and their aesthetic faculties, and that is what leads to succeed the aimed linguistic communication.